Implementasi BIM 5D dalam Perancangan Rumah RISHA Menggunakan Autodesk Revit - Cahyaning Kilang Permatasari; Muhammad Ryan Iskandar; Novita Novita (Jurnal Talenta Sipil, 2026)
The need for efficient and integrated housing planning has encouraged the adoption of digital technologies in the construction sector, particularly in the development of Rumah Instan Sederhana Sehat (RISHA). Conventional planning practices for RISHA often result in inconsistencies between drawings, quantity calculations, and cost estimates. This study aims to implement Building Information Modeling (BIM) 5D using Autodesk Revit in the design of RISHA housing to achieve integrated and accurate planning. The research employed a descriptive–analytical method with quantitative and qualitative approaches, involving BIM 3D modeling, quantity take-off analysis, and cost estimation based on the AHSP of Ministry of Public Works and Housing Regulation No. 8 of 2023, adjusted to local unit prices in Klaten Regency. The results indicate that the application of BIM 5D produces a construction cost estimate of approximately Rp 122.135.014,70 for a ±36 m² RISHA house and improves design visualization and data consistency. The study concludes that BIM 5D is effective for the design of modular precast RISHA housing and contributes to the advancement of digital transformation in housing construction planning in Indonesia.